Desferrioxamine B-Mediated Pre-Clinical In Vivo Imaging of Infection by the Mold Fungus Aspergillus fumigatus - Misslinger, Matthias; Petrik, Milos; Pfister, Joachim; Hubmann, Isabella; Bendova, Katerina; Decristoforo, Clemens; Haas, Hubertus (Journal of fungi (Basel, Switzerland), 2021)
Fungal infections are a serious threat, especially for immunocompromised patients. Early and reliable diagnosis is crucial to treat such infections. The bacterially produced siderophore desferrioxamine B (DFO-B) is utilized by a variety of microorganisms for iron acquisition, while mammalian cells lack the uptake of DFO-B chelates. DFO-B is clinically approved for a variety of long-term chelation therapies. Recently, DFO-B-complexed gallium-68 ([68Ga]Ga-DFO-B) was shown to enable molecular imaging of bacterial infections by positron emission tomography (PET). Here, we demonstrate that [68Ga]Ga-DFO-B can also be used for the preclinical molecular imaging of pulmonary infection caused by the fungal pathogen Aspergillus fumigatus in a rat aspergillosis model. Moreover, by combining in vitro uptake studies and the chemical modification of DFO-B, we show that the cellular transport efficacy of ferrioxamine-type siderophores is impacted by the charge of the molecule and, consequently, the environmental pH. The chemical derivatization has potential implications for its diagnostic use and characterizes transport features of ferrioxamine-type siderophores.
Keywords: gallium-68; imaging; PET; infection; invasive pulmonary aspergillosis; siderophore; positron emission tomography; pH; Aspergillus fumigatus; desferrioxamine B